The Determinants of Price, Product Quality, Promotion, and Brand Awareness on Purchase Intention for Nusakita Cooking Oil in Jabodetabek - Ariq Athallah; Hardiana Widyastuti (Universitas Negeri Semarang, 2024)
This study aims to identify the characteristics of respondents and analyze the effect of price, product quality, promotion, and brand awareness on consumer buying interest in Nusakita cooking oil in the Jabodetabek area. Indonesia, as a major producer of palm oil, has a highly competitive cooking oil industry due to the increasing needs of the community. This study employs a quantitative approach to analyze the effects of price, product quality, promotion, and brand awareness on purchase intention for Nusakita cooking oil products in Jabodetabek. Using a non-probability voluntary sampling method, data from 235 respondents were collected through online and offline questionnaires. Descriptive statistics and SEM-PLS were applied for data analysis, revealing significant positive effects of product quality, promotion, and brand awareness on purchase intention. The results showed the need for Nusakita to prioritize enhancing product quality and increasing brand visibility to drive consumer interest. Strengthening promotional efforts, such as offering discounts or engaging in targeted marketing campaigns, is also recommended. These strategies can help establish Nusakita as a trusted cooking oil brand in a competitive market.